Psychometric properties of the Korean version of the oncofertility barriers scales among nurses: A methodological study - Hae Jeong An; Yoonjung Kim (Elsevier, 2023)
Objective: This study aimed to examine the psychometric properties of the Korean version of the Oncofertility Barrier Scale (K-OBS). Methods: This methodological study investigated the validity and reliability of the K-OBS for measuring barriers to oncofertility care among nurses. A total of 270 nurses who had experience in rendering nursing care to cancer survivors were recruited, and the instrument was translated, assessed for content validity, and tested using a preliminary survey. Construct validity was established through explanatory factor analysis. Convergent validity and discriminant validity were analyzed using a multitrait-multimethod (MTMM) matrix. Reliability was assessed using Cronbach's alpha and McDonald's omega. Results: The K-OBS demonstrated satisfactory validity and reliability, with seven factors, including 27 items explaining 60.42% of the total variance, a Cronbach's alpha of 0.86, and a McDonald's omega of 0.83. The seven factors were labeled, "Lack of information and education" (8 items), "Rigid thinking toward oncofertility care" (5 items), "Cancer patient stereotypes" (4 items), "Insufficient support" (4 items), "Desire for fertility preservation" (2 items), "Interrupted oncofertility care" (2 items), and "Fertility risk" (2 items). Conclusions: The results of this study indicate that the K-OBS may be a suitable instrument with acceptable validity and reliability for evaluating barriers to oncofertility among Korean nurses. This instrument can be used to identify obstacles that make oncofertility care difficult, thereby contributing to new insights for improving the future quality of oncofertility care in Korea.